Mechanistic Study on the Possible Role of Embelin in Treating Neurodegenerative Disorders - Anika; Arora, Rimpi; Virendra, Sharma A.; Chawla, Pooja A. (CNS & Neurological Disorders - Drug Targets, 2024)
Embelin (EMB) (2,5-Dihydroxy-3-undecyl-1,4-benzoquinone) is a natural benzoquinone extracted mainly from Embelia ribes (ER) and appear as vivid orange dots beneath the fruit's pericarp. It is being used to treat various diseases since ancient times in India. It has been ascribed as one of the 32 ayurvedic drugs of national importance in the National Medicinal Plant Board set up by the Government of India under the Ministry of Indian System of Medicine and Homeopathy. Embelin prevents neuronal oxidative damage by decreasing the peroxidation of lipids. Along with having antioxidant properties, it also prevents the production of amyloid-protein-related fibrils and blocks the progression of inflammatory cascades. Due to embelin's ability to cross the blood-brain barrier, its neuroprotective effects have been studied in the past using in vitro models of neuronal disorders such as convulsion and epilepsy, Alzheimer's disease, anxiety and depression, traumatic brain injury, cerebral ischemia, Huntington's disease, and multiple sclerosis. In addition to its neuroprotective effects, its role as an antitubercular, anti-cancer, antioxidant, astringent, anti-inflammatory, anti-bacterial, contraceptive, carminative, diuretic, and anthelmintic agent has also been studied. With docking studies and recent advancements in formulations of embelin including polyethylene and embelin micelles and embelin noisome preparations, embelin can prove to be a promising compound for its therapeutic actions in a wide range of diseases and disorders. The findings of docking studies suggest the binding ability of embelin to be similar to the standard drug in their respective disorders. In this review and docking analysis, we bring an outline of scientific evidence concerning the neuroprotective actions of embelin, still, further research is required for its prospective as a chief compound in clinical approaches.
Keywords: natural treatment